2020
DOI: 10.1093/hmg/ddz296
|View full text |Cite
|
Sign up to set email alerts
|

The intellectual disability PAK3 R67C mutation impacts cognitive functions and adult hippocampal neurogenesis

Abstract: Abstract The link between mutations associated with intellectual disability (ID) and the mechanisms underlying cognitive dysfunctions remains largely unknown. Here, we focused on PAK3, a serine/threonine kinase whose gene mutations cause X-linked ID. We generated a new mutant mouse model bearing the missense R67C mutation of the Pak3 gene (Pak3-R67C), known to cause moderate to severe ID in humans without other clinical signs and investigated hippocampal-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…In addition, we did not observe a deficit in spatial or fear memory acquisition or recall as evidenced by our Morris Water Maze and fear conditioning results. Our spatial memory test supports the results of a recent study that demonstrated that mPAK3 protein selectively impaired strained, massed spatial memory training protocols but not distributed spatial training such as our training protocol [15]. On the other hand, fear memory acquisition and retrieval may also be compensated by alternative pathways due to its evolutionary importance for survival [50].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, we did not observe a deficit in spatial or fear memory acquisition or recall as evidenced by our Morris Water Maze and fear conditioning results. Our spatial memory test supports the results of a recent study that demonstrated that mPAK3 protein selectively impaired strained, massed spatial memory training protocols but not distributed spatial training such as our training protocol [15]. On the other hand, fear memory acquisition and retrieval may also be compensated by alternative pathways due to its evolutionary importance for survival [50].…”
Section: Discussionsupporting
confidence: 89%
“…Genetic studies have shown that various gene mutations of PAK3 cause moderate to severe ID with abnormal dendritic development and synapse formation without affecting the gross brain development in human patients [ 9 , 10 , 11 ]. In addition, mouse models generated based on the manipulations of PAK3 and its close family members display impaired synaptic function, including spine morphology and synaptic plasticity, as well as cognitive deficits, without alterations in the gross anatomy of the brain, as seen in human patients [ 12 , 13 , 14 , 15 , 16 , 17 ]. Therefore, these animal models provide powerful tools for specifically investigating the molecular processes underlying cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein kinases such as Pak3, Limk1, ERK, and RSK2 have been implicated in intellectual disability [ 56 , 57 ]. However, the mechanisms by which these protein kinases are involved in intellectual disability are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the latter variant impacts cognitive functions and adult hippocampal neurogenesis [ 126 ]. Likewise, Pak3 -KO mice have no apparent defects in the actin cytoskeleton, but showed impaired hippocampal LTP, together with learning and memory deficits [ 127 ].…”
Section: Cytoskeleton Functions In Neuronal Developmentmentioning
confidence: 99%